Improved third harmonic nonlinear optical process upon e-beam irradiation in Cl: ZnO thin films. (1st August 2020) - Antony, Albin; Poornesh, P.; Jedryka, J.; Ozga, K.; Ani, Aninamol; Kulkarni, Suresh D.; Sanjeev, Ganesh; Chandra Petwal, Vikash; Verma, Vijay Pal; Dwivedi, Jishnu
Abstract: We report the tuning of third-harmonic generation and nonlinear absorption process in Cl doped ZnO (Cl: ZnO) thin films by energetic electron beam irradiation. The structural studies outcomes the stability of the films based on the nominal variations observed in structural parameters on irradiation. The absorption edge shows a redshift at higher irradiation dosage and bandgap of the film shows a drop from 3.28 eV to 3.22 eV at 20 kGy dosages. The morphology of the films has undergone a drastic change on irradiation and grains are found to be shattered and islands are formed at different regions of the scan area. The photoluminescence (PL) spectra show substantial change after the irradiation and number of emissions centres decreased along with peak broadening effect. The studies confirm that radiative defects in the films decreased which in turn give rise to enhancement of non-radiative defects. The Raman spectra depicts three phonon modes E2H -E2L, A1 (TO) and E2H similar to unirradiated films. The E2H mode peak has dominated in all the irradiated films confirming the hexagonal wurtzite structure of the films. On irradiation, the asymmetry observed in the core level O 1s XPS spectra has changed and a single peak positioned around 529.8 eV was observed indicating the quenching of oxygen-related defects. Third harmonic generation studies exhibit an enhancement in the THG intensity upon electron beam incorporation attributed to optical absorption and excitonic effects. Open aperture Z-scan measurement shows a high βeff of 31 × 10 -2  cm/W at 20 kGy irradiated films due to enhanced scattering induced nonlinear absorption phenomena. The enhanced nonlinear optical properties exhibited by Cl: ZnO thin films show promising applications of grown material in frequency conversion and optical filtering devices. Highlights: Enhanced THG signal intensity upon EBI due to optical absorption and excitonic effects. Higher βeff value on irradiation by scattering induced nonlinear absorption phenomena. Decrement of oxygen related defects after irradiation.